2021
DOI: 10.1503/jpn.200226
|View full text |Cite
|
Sign up to set email alerts
|

Early-life experiences altered the maturation of the lateral habenula in mouse models, resulting in behavioural disorders in adulthood

Abstract: Background: Abnormally high activity in the lateral habenula causes anxiety- or depression-like behaviours in animal experimental models. It has also been reported in humans that excessive stress in early life is correlated with the onset of psychiatric disorders in adults. These findings raise the question of whether maturation of the lateral habenula is affected under the influence of early-life experiences, which could govern behaviours throughout life. Methods: We examined the maturation of the lateral ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…These neurons have been shown to inhibit other LHb neurons to promote aggressive behaviour in mice (Flanigan et al, 2020) which, as mentioned earlier, can be interpreted as a reward-seeking behaviour (Golden et al, 2016). We and others have recently shown that some LHb neurons which express the well-known cortical interneuron marker parvalbumin (Tremblay et al, 2016) are GABAergic and inhibit local LHb neurons (Webster et al, 2020;Nakamura et al, 2021). These neurons are likely distinct from the aforementioned population of GAD-2 expressing neurons in that they are confined to the lateral LHb and also express the vesicular GABA transporter (VGAT; Webster et al, 2020), another well-known marker of inhibitory neurons, but largely do not express GAD-2 (Nakamura et al, 2021).…”
Section: Locally-targeting Inhibitory Lhb Neuronsmentioning
confidence: 74%
See 2 more Smart Citations
“…These neurons have been shown to inhibit other LHb neurons to promote aggressive behaviour in mice (Flanigan et al, 2020) which, as mentioned earlier, can be interpreted as a reward-seeking behaviour (Golden et al, 2016). We and others have recently shown that some LHb neurons which express the well-known cortical interneuron marker parvalbumin (Tremblay et al, 2016) are GABAergic and inhibit local LHb neurons (Webster et al, 2020;Nakamura et al, 2021). These neurons are likely distinct from the aforementioned population of GAD-2 expressing neurons in that they are confined to the lateral LHb and also express the vesicular GABA transporter (VGAT; Webster et al, 2020), another well-known marker of inhibitory neurons, but largely do not express GAD-2 (Nakamura et al, 2021).…”
Section: Locally-targeting Inhibitory Lhb Neuronsmentioning
confidence: 74%
“…We and others have recently shown that some LHb neurons which express the well-known cortical interneuron marker parvalbumin (Tremblay et al, 2016) are GABAergic and inhibit local LHb neurons (Webster et al, 2020;Nakamura et al, 2021). These neurons are likely distinct from the aforementioned population of GAD-2 expressing neurons in that they are confined to the lateral LHb and also express the vesicular GABA transporter (VGAT; Webster et al, 2020), another well-known marker of inhibitory neurons, but largely do not express GAD-2 (Nakamura et al, 2021). Note however that the expression patterns of GABAergic markers within the LHb appears to differ between mice and rats (Quina et al, 2020), with VGAT expression in rats observed in the medial LHb and GAD-2 expression largely absent (Zhang et al, 2018;Quina et al, 2020).…”
Section: Locally-targeting Inhibitory Lhb Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the circuit level, previous SAM-LB adversity prevented maternal buffering of the mesolimbic dopamine (DA) circuit, including the ventral tegmentum (VTA), nucleus accumbens, and BLA, as well as the interface between the medial prefrontal cortex and the BLA (Barr et al, 2009 ). Recently, research by our group has expanded this circuit to show that adversity also prevents the mother's ability to regulate the lateral habenula (LHb), an important negative regulator of the midbrain DA circuitry (Baker and Mizumori, 2017 ; Fakhoury, 2017 ; Hu et al, 2020 , 2022 ; Germann et al, 2021 ; Nakamura et al, 2021 ; Packard et al, 2021 ).…”
Section: Animal Models Of Early Caregiving Adversity: Approaches and ...mentioning
confidence: 99%
“…PV expression shows up within the first two postnatal weeks following birth in rodents (Seto-Ohshima et al, 1990;de Lecea et al, 1995;Fishell, 2007;Marín, 2012;Bartolini, et al, 2013;Wong et al, 2018) and matures through the early juvenile period, marked by an increase in both intensity of PV expression and the number of PV-positive interneurons, as well as the formation and strengthening of PV interneuron synapses through perineuronal net (PNN) deposition, which is associated with the eventual closure of critical windows (Favuzzi et al, 2017;Bucher et al, 2021). Indeed, it has been hypothesized that PV-positive interneuron dysregulation during these developmental windows (Marín, 2012;Bartolini et al, 2013;Canetta et al, 2016;Santiago et al, 2018;Murthy et al, 2019;Gildawie et al, 2020;Ohta et al, 2020;Gildawie et al, 2021;Guadagno et al, 2021;Klimczak et al, 2021;Nakamura et al, 2021) be one of the key pathophysiological mechanisms contributing to the neurodevelopmental origins of multiple psychiatric disorders (Ferguson and Gao, 2018;Ruden et al, 2021), such as major depression (Fogaça and Duman, 2019;Spijker et al, 2020), bipolar disorder (Konradi et al, 2011), autism (Contractor et al, 2021) and schizophrenia (Lewis et al, 2012;Dienel and Lewis, 2019).…”
Section: Introductionmentioning
confidence: 99%